1999
DOI: 10.1007/s003300050880
|View full text |Cite
|
Sign up to set email alerts
|

Is capsular retraction a specific CT sign of malignant liver tumor?

Abstract: The aim of this study was to assess if a liver capsular retraction is a specific CT sign in malignant hepatic tumors. The authors reviewed retrospectively 320 hepatic CT scans obtained in 300 patients during a 3-year period. These patients presented with benign (n = 64) or malignant (n = 236) hepatic tumors. In 7 patients we found retraction of the capsule surrounding the tumor. All these tumors were histologically proven as malignant lesions: 4 metastases (none being chemically treated), 2 peripheral cholangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Capsular retraction adjacent to hepatic tumours is uncommon, with a reported frequency of 2.0-2.8% [10], and is thought to be caused by tumoural necrosis and desmoplastic reaction [11].…”
Section: Discussionmentioning
confidence: 99%
“…Capsular retraction adjacent to hepatic tumours is uncommon, with a reported frequency of 2.0-2.8% [10], and is thought to be caused by tumoural necrosis and desmoplastic reaction [11].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, capsular retraction was found in association with true lesions and also in association with pseudolesions. Capsular retraction has been reported to be very suggestive of the diagnosis of actual lesions, and some studies suggest that it can be more frequently found in cases of malignant neoplasms [35,36]. However, this finding can be found either in malignant tumours or in benign ones [37][38][39].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, hepatic metastases from breast carcinoma were less likely because of a normal CA 15.3 serum level. Retraction of the liver capsule adjacent to hepatic tumor has been reported in a variety of primary malignant (intrahepatic cholangiocarcinoma, epithelioid hemagioendothelioma) and secondary hepatic tumors (neuroendocrine tumors) [5][6][7][8]. This finding can also be observed in untreated liver metastases from breast cancer that may result in lobulated contours and morphologic changes of the liver, displaying the so-called ''hepar lobatum'' pattern [9].…”
mentioning
confidence: 89%